Urgensi Pembentukan Undang-undang tentang Pasar Modal Syariah - Kurniawan Desiarto (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
This paper confirms that the growth of the Islamic economy in the midst of the global crisis shows the development of Islamic capital markets not only in Muslim-majority countries, but also in secular countries such as America. This paper emphasizes the urgency of the establishment of a Law on Islamic Capital Markets. Although the development of the Islamic capital market has increased, the regulation of the existence of the Islamic capital market has not yet been regulated in law. Meanwhile, Law No. 8 of 1995 concerning the Capital Market found several shortcomings. Whereas activities in the capital market can lead to conflicts or disputes. In its development, disputes in the capital market can be resolved through non-litigation channels, one of which is arbitration that has not been fully accommodated in the Capital Market Law. The existence of regulations regarding the Islamic capital market with the legal basis of a law as well as to strengthen sharia arbitration as an alternative dispute resolution in the Islamic capital market. Abstrak: Karya ilmiah ini menegaskan bahwa adanya pertumbuhan perekonomian Islam di tengah krisis global menunjukkan perkembangan pasar modal syariah tidak hanya di berbagai negara yang mayoritas muslim, namun juga di negara sekuler seperti Amerika. Tulisan ini lebih menekankan pada urgensi pembentukan Undang-undang tentang Pasar Modal Syariah. Perkembangan pasar modal syariah meskipun mengalami peningkatan, tetapi pengaturan terhadap keberadaan pasar modal syariah belum diatur dalam Undang-undang. Sementara Undang-undang No.8 Tahun 1995 tentang Pasar Modal ditemukan beberapa kekurangan. Padahal kegiatan di pasar modal dapat menimbulkan konflik atau sengketa. Pada perkembangannya, sengketa dalam pasar modal dapat diselesaikan melalui jalur non litigasi salah satunya dengan arbitrase belum sepenuhnya diakomodir dalam Undang-undang Pasar Modal. Adanya pengaturan mengenai pasar modal syariah dengan dasar hukum sebuah Undang-undang sekaligus untuk memperkuat arbitrase syariah sebagai alternatif penyelesaian sengketa di pasar modal syariah.